Universality and difference of electronic and spin transport properties at the irradiated oxide surface. (23rd August 2017) - Wang, Qiuru; Zhang, Wanli; Peng, Bin
Abstract: The ion irradiation technique is utilized to modify the surface structure of transition metal oxides (TMOs), including SrTiO3 and TiO2 . After low-energy Ar + ion bombardment, oxygen vacancies are introduced into the TMO surface layer, and their resistance decreases with increasing irradiation time. For the two oxides, the temperature-dependent resistivity exhibits different conducting behaviors. Due to the generation of an electron-doped quasi-2D surface layer, the voltage signals of the inverse Rashba–Edelstein effect are extracted in the ion-irradiated TMO with ferromagnetic permalloy films, and the spin transport parameters are respectively calculated from the ferromagnetic resonance measurement data.